PENGARUH MEDIA PEMBELAJARAN BERBASIS AUDIO VISUAL TERHADAP MINAT BELAJAR PESERTA DIDIK MATERI EKSRESI PADA MANUSIA DI SMAN 2 MEREUBO - Rufa hera; Rita Oktavia; Agus Kistian (Jurnal Bionatural, 2024)
Biology is a science that generally contains abstract studies. The concept of biology urgently needs significant and interesting teaching media to encourage students to study biology comprehensively and in-depth. Currently, the use of learning media in the study of biological sciences has not been maximized by educators in schools, especially audiovisual-based media. The purpose of this study is to find out "The Effect of Audio Visual Media of Excretory System Materials on Humans to Increase the Learning Interest of Class X Students at SMAN 2 Meureubo”. The subject used is a student of class X science of SMAN 2 Meureubo. The results of the research obtained are that the use of audio-visual- based learning media has a significant effect on the learning outcomes of students with excretory system material. The results of the statistical test show that there is a significant influence between the use of audio-visual media and the absence of audio-visual media on student learning outcomes.